The influence of the Turkish Republic's Revolutions on accounting applications (1926-1928) - (:unkn) unknown (Bogazici Universitesi, 2007)
The purpose of this article is to review the influence of Atatürk' s revolutions, which were made during the period of the foundation of the Turkish Republic, on the modernization of the concept of accounting and accounting applications. The actors of the Republic made an effort to ensure the community attained a contemporary structure through social and administrative reforms, on the one hand, and took measures in order to strengthen the economic infrastructure on the other. The measures included such legislative actions as the Turkish Commercial Code and the Income Tax Code. The new codes and the transition to the Latin alphabet all positively influenced the modernization of accounting practice and education, and the adoption of the double-entry recording method. These laws, by mandating the keeping of records of transactions in Turkish extended the application of accounting throughout the country. In this article, the developments between the years 1926 and 1928, when the relevant legislative regulations were made, are reviewed.
Keywords: Atatürk revolutions; Double-entry recording method; Turkish Commercial Code